2016
DOI: 10.1080/19443994.2015.1029525
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale treatment of textile wastewater by combined biological-adsorption process

Abstract: A B S T R A C TDye pigments are the main pollutants in textile industry wastewaters. Dye reduction or completely removal from the wastewater is the biggest challenge in this industry. This study was carried out by combined biological-adsorption system. Activated sludge with extended aeration as biological and slow filtration as adsorption process was used. In activated sludge system, different hydraulic retention times (HRT) were investigated (18, 24, 30, and 36 h). The results revealed that by increasing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Improper discharge of printing and dyeing wastewater may endanger aquatic environment and human health. With current strict discharge standards, new requirements have been put forward for the treatment of printing and dyeing wastewater accordingly (Mirbagheri and Charkhestani 2015, Periyasamy et al 2018, Ramlow et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Improper discharge of printing and dyeing wastewater may endanger aquatic environment and human health. With current strict discharge standards, new requirements have been put forward for the treatment of printing and dyeing wastewater accordingly (Mirbagheri and Charkhestani 2015, Periyasamy et al 2018, Ramlow et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the great importance of reuse of agro-industrial waste, a number of studies have indicated the use of biomass to adsorb pollutants with significant results, demonstrating high efficiency in the removal of pollutants even in small quantities [16]. The adsorption capacity of these nonconventional adsorbents is due to the presence of biopolymers such as polysaccharides, lignin, hemicelluloses and cellulose [17].…”
Section: Introductionmentioning
confidence: 99%